2015
DOI: 10.1186/s40349-015-0042-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive magnetic resonance-guided high intensity focused ultrasound ablation of a vascular malformation in the lower extremity: a case report

Abstract: IntroductionTherapy of choice for symptomatic vascular malformations consists of surgery, sclerotherapy, or embolization. However, these techniques are invasive with possible complications and require hospitalization. We present a novel non-invasive technique, i.e., magnetic resonance-guided high-intensity focused ultrasound (MR-HIFU) ablation, for the treatment of a vascular malformation in a patient. This technique applies high-intensity sound waves transcutaneously to the body and is fully non-invasive. MRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
1
12
0
1
Order By: Relevance
“…The present results are consistent with those of a recently published case report (14) describing successful treatment of a painful small venous malformation of the medial left calf with the use of MR–guided high-intensity focused US. The authors reported pain relief and a 30% reduction in vascular malformation volume.…”
Section: Discussionsupporting
confidence: 92%
“…The present results are consistent with those of a recently published case report (14) describing successful treatment of a painful small venous malformation of the medial left calf with the use of MR–guided high-intensity focused US. The authors reported pain relief and a 30% reduction in vascular malformation volume.…”
Section: Discussionsupporting
confidence: 92%
“…2A), suggesting its vital clinical role in early manifestation of PCa exacerbation [35][36][37][38][39]. Virtually, PCa was confirmed by MRI when low-signal nodules were present within peripheral zone that was intense in T2W1.…”
Section: Discussionmentioning
confidence: 82%
“…25,26 Besides, some researches have shown novel ablative techniques. 27 For small lesions located in some difficult situations, neodymium yttrium-aluminum-garnet laser therapy has been used. 28 These new encouraging methods showed their applications toward VMs but further clinical testing is necessary.…”
Section: Discussionmentioning
confidence: 99%